2017
DOI: 10.21272/jnep.9(5).05030
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensional Effect in Trimethylsilylated Silica Nanoparticles

Abstract: The synthesis of organosilicas with a predetermined ratio of trimethylsilyl groups and silanols using trimethyloxysilane and acetic acid as a modifier and catalyst respectively was carried out in this work. It has been established that grafted trimethylsilyl groups influence the structural state of silica. The reducing of the surface tension and, consequently, the Laplace pressure in the SiO2 globules leads to an increase in the valence angle in the siloxane bridges and the length of Si -O-bond. This dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Chemisorbed TMS-groups reduce a surface tension and Laplace pressure in SiO 2 particles [22]. This, in turn, leads to an increase in the valence angle in Si -O -Si bridges and a reduction in the siloxane bond length in SiO 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemisorbed TMS-groups reduce a surface tension and Laplace pressure in SiO 2 particles [22]. This, in turn, leads to an increase in the valence angle in Si -O -Si bridges and a reduction in the siloxane bond length in SiO 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing the particles' size and increasing their density provides an increase in the number of atoms per unit area of the particles' surface, and the number of adsorption centers in the surface layer. This dimensional effect is manifested by displacement in the short-wave region of absorption bands in the infrared spectra of modified silica, associated with asymmetric oscillations of tetrahedra SiO 4 ( ν a ) and deformation oscillations of siloxane bridges (ν OSiO ) [22]. Simulation of the structure of a number clusters of silica surface by quantum chemistry methods revealed that there is significant change in the electrostatic potential distribution during the consistent substitution of surface silanols by the TMS-groups [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations